Partisipasi Masyarakat Dalam Rangka Penanggulangan Pencemaran Sungai - Elvi Roza Syofyan (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2019)
River is a natural and man made watercourse in network of river flow and its water. The use of water in upper catchment will reduce the opportunity in using it downstream the catchment. Pollution in headwater would result in sosial cost in the downstream area. In turn if the society in the upper catchment preserve the river, the society downsteam the catchment will be benefit from it. Water is a natural resouces to fulfill life need of the society. Therefore, it needs to be preserved to benefit life of man as well other living matters. To preserve or attain water quality which can be used sustainably by the society with acceptable water quality level, there needs to preserve and control water by with preservation and mitigation of river pollution.